Visualization of multidimensional numerical arrays of solid-state objects - Ramašauskas, Olegas (Lietuvos matematikos rinkinys, 2013)
This article is intended for math and computer science subjects study deepening and understanding of multidimensional computer graphics environment. The paper describes multidimensional numeric arrays visualization using object-oriented programming tools. The method allows the multidimensional numeric arrays stored data to simulate virtual reality products which, in turn, can become the reference now intensively developed new embedded system components. Shown an another option to simulate the multidimensional visual objects that may be transformed from capturing or graphically present on the computer screen using a new computational mathematics packages for solving advanced computer graphics tasks. It seems comfortable to use new estimated mathematics programs and packages, which already are enriched with digital image processing tools, allowing create a various objects of the real world.